How Code Words Work - (:unkn) unknown (My University, 2020)
This paper aims at giving a novel theory of code words. I start with an explanation of what code words are by introducing four primary features of them. Then, I turn to three major theories of code words: those offered by Stanley, Khoo, and Saul. I show how each of these theories falls short of giving a thorough account of all features of code words. Finally, drawing on these lessons, I will formulate a new theory which suggests that code words are polysemous.